2019
DOI: 10.1097/ijg.0000000000001298
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Goniotomy With Kahook Dual Blade in Patients With Uveitis-associated Ocular Hypertension

Abstract: Precis: In a small case series of patients with uveitis-associated ocular hypertension (OHTN) or glaucoma, goniotomy with Kahook Dual Blade (KDB) was an effective surgical treatment option for lowering intraocular pressure (IOP). Purpose: The purpose of this study is to review the success of goniotomy using the KDB with trabecular meshwork (TM) excision in lowering the IOP of patients with uveitis-associated OHTN or glaucoma. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 32 publications
3
32
3
1
Order By: Relevance
“…The iStent is labeled for use in eyes with mild to moderate OAG,3 while KDB excisional goniotomy can successfully lower IOP across the spectrum of severity including advanced OAG 610. The KDB is also effective in challenging secondary glaucoma such as angle-closure9,10 and uveitic glaucoma,11 and in contrast to the iStent’s label, KDB excisional goniotomy can be performed as a standalone procedure 6…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The iStent is labeled for use in eyes with mild to moderate OAG,3 while KDB excisional goniotomy can successfully lower IOP across the spectrum of severity including advanced OAG 610. The KDB is also effective in challenging secondary glaucoma such as angle-closure9,10 and uveitic glaucoma,11 and in contrast to the iStent’s label, KDB excisional goniotomy can be performed as a standalone procedure 6…”
Section: Discussionmentioning
confidence: 99%
“…The Kahook Dual Blade (New World Medical, Rancho Cucamonga, CA) is a surgical knife designed to excise a strip of TM in a procedure known as excisional goniotomy. The procedure can be performed at the time of cataract surgery or as a standalone procedure,6 is effective in mild to advanced OAG,69 and has been performed successfully in secondary glaucomas as well 911. In clinical studies, KDB-Phaco lowered IOP by ~25% and medications by ~45–65% 7,10,12,13.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28] When the uveitic glaucoma patients with elevated IOP were studied, only about 38% of them achieved the 20% reduction mark. 29 Although the retrospective studies referenced above focus on KDB as a standalone procedure, KDB has been shown to be similarly effective with cataract surgery. Using the 20% IOP reduction mark as a success standpoint, phaco/KDB demonstrated that 72% of the eyes had ≥20% IOP reduction, which was not statistically different from KDB alone in which 69% had ≥20% IOP reduction.…”
Section: Kahook Dual Blade ®mentioning
confidence: 99%
“…24,26,27,30 In terms of medication reduction, as a standalone procedure, KDB may reduce medications by 0-1, and phaco/KDB may reduce medications by 0.1-2.1 in glaucoma of all types and severities. 23,24,[28][29][30] In general, the severity and type of glaucoma have not been significantly correlated with KDB success rates, although most studies were done in mild-to-moderate glaucoma or OHTN patients. 28,30 KDB has been shown to be effective in severe/ refractive OAG and ACG, reducing IOP by up to 24% in these patients.…”
Section: Kahook Dual Blade ®mentioning
confidence: 99%
See 1 more Smart Citation